Clinical Outcomes of Critically Ill Patients in a Level II Closed Intensive Care Unit: A Retrospective Observational Study from a Provincial Hospital in Nepal - Dhakal, Sujan; Karki, Kiran; Nepal, Muna; Gautam, Elija; Shahi, Tejash; Bajracharya, Joshan Lal (Journal of Nepalese Society of Critical Care Medicine, 2026)
Background and aims: Critical care services in provincial, resource- constrained contexts often lack strict performance measures, which impedes quality improvement initiatives. Existing research focuses mostly on tertiary care facilities, leaving a significant gap in understanding outcomes at the local level. The intensive care unit (ICU) at Bhadrapur Provincial Hospital, located in Nepal’s eastern area bordering India, is a Level II closed unit managed by a consultant anaesthesiologist. This study evaluates the demographics, clinical characteristics, resource utilization, and important outcomes across two consecutive years. Methods: For this retrospective observational study, data were extracted from ICU admission-discharge registers and electronic medical records. Descriptive statistics were utilized to summarize patient profiles and outcomes, with a comparative analysis conducted for the two years, April 2023 - April 2025. Results: In a total of 528 admissions, the mean age was 50.4±19.7 years, with a male predominance of 57.2%. Medical cases dominated the admissions, and the median length of ICU stay was 3 days [IQR 1-4]; toxicological cases comprised 21.2% of the total admissions. Crude ICU mortality rate increased significantly from 17.3% in the first year to 24.8% in the succeeding year (p = 0.042). The unit operated at a bed occupancy rate of 82.9%. Conclusion: The Level II provincial ICU is predominantly responsible for the management of acute medical and toxicological admissions. The average mortality rate of 20.7% is consistent with that of national tertiary centers. Strengthened referral networks, expanded life support capabilities, and standardised protocols are essential for improving outcomes.